Business solutions on demand transform the business to deliver real customer value - Cerasale, Mark Vincent 1969- (Gale virtual reference library, 2004)
Based partly on IBM's own transformation, and partly on the transformations that IBM has helped its clients to achieve, this groundbreaking book shows how companies can increase sales and improve margins by introducing a range of solutions. Drawing on IBM's extensive experience of working with clients all over the world, the book is packed with examples from a diverse range of industries.